WT1‐interacting protein inhibits cell proliferation and tumorigenicity in non‐small‐cell lung cancer via the AKT/FOXO1 axis. Issue 5 (22nd February 2019) - Wu, Zhiqiang; Qiu, Minghan; Mi, Zeyun; Meng, Maobin; Guo, Yu; Jiang, Xiangli; Fang, Jiaping; Wang, Hui; Zhao, Jinlin; Liu, Zhuang; Qian, Dong; Yuan, Zhiyong
Abstract : Lung cancer is the most common cancer and the leading cause of cancer‐related death worldwide; hence, it is imperative that the mechanisms underlying the malignant properties of lung cancer be uncovered in order to efficiently treat this disease. Increasing evidence has shown that WT1‐interacting protein (WTIP) plays important roles both physiologically and pathologically in humans; however, the role of WTIP in cancer is unknown. Here, we investigated the role and mechanism of WTIP in cell proliferation and tumorigenesis of non‐small‐cell lung cancer (NSCLC). We report that WTIP is a tumor suppressor in human NSCLC. We found that WTIP expression was significantly reduced in both NSCLC cell lines and clinical specimens compared to that in normal controls; this reduction was largely attributed to promoter hypermethylation. Downregulation of WTIP significantly correlates with poor prognosis and predicts a shorter overall survival and progression‐free survival among NSCLC patients. Moreover, ectopic overexpression of WTIP dramatically inhibits cell proliferation and tumorigenesis in vitro and in vivo ; conversely, depletion of WTIP expression shows the opposite effects. Mechanistically, WTIP impairs AKT phosphorylation and activation, leading to enhanced expression and transcriptional activity of FOXO1, which further increases p21Cip1 and p27Kip1, and decreases cyclin D1, which consequently results in cell cycle arrest. Collectively, the results of the current study indicate that WTIP is an important proliferation‐related gene and that WTIP expression may represent a novel prognostic biomarker for NSCLC. Abstract : Promoter methylation represses expression of WT1‐interacting protein (WTIP). Ectopic overexpression of WTIP impairs AKT phosphorylation and activation and enhances expression and transcriptional activity of FOXO1; this leads to increases in p21Cip1 and p27Kip1, and decreases in cyclin D1, which in turn results in reduced cell proliferation and tumorigenesis. This study indicates that WTIP has tumor‐suppressive effects and may be a novel prognostic biomarker for non‐small‐cell lung cancer.